Cytotoxicity and genotoxicity studies of synthesized amino acid thiourea derivatives on acanthamoeba spp. and human corneal epithelial cells - Ibrahim, Maizatul Akma; Nordin, Mohd Shukor; Mat Amin, Nakisah; Mohd Yusof, Mohd Sukeri (2015)
Two newly-synthesized amino acids thiourea derivatives; 2-(3-benzoylthioureido)-3-mercaptopropanoic acid and 2-(3-benzoylthioureido)-4-(methylthio)butanoic acid, which were labeled as M1 and M2 respectively, were evaluated for their potential as anti-amoebic agent, aiming for a new discovery in amoebic keratitis treatment. The compounds were tested on Acanthamoeba castellanii (CCAP 1501/2A) and Acanthamoeba sp. (Hospital Kuala Lumpur isolate), and also on human corneal epithelial cells (HCEC). Experiments conducted consisting of IC50 determination by eosin dye and MTT assay, morphological observation by light microscopy, evaluation of membrane integrity by acridine orange/propidium iodide staining, mode of cell death determination by DNA fragmentation test and assessment of DNA damage by alkaline comet assay. The IC50 obtained for M1 were 6.26 μM for A. castellanii, and 9.00 μM for Acanthamoeba sp. (HKL isolate) while for M2 the values were 6.97 and 8.63 μM respectively, indicating that these compounds are cytotoxic against both Acanthamoeba. They shortened acanthopodia structures, transformed the amoeba cells to become rounded, and exhibited no distinct vacuoles and nucleus. The membrane integrity was also disrupted, making them non-intact, and promoted apoptosis in amoeba but did not significantly affected the DNA. Both thiourea derivatives showed moderate cytotoxicity toward HCEC with IC50 at 132.69 and 98.20 μM respectively. The compounds did not significantly alter corneal cells’ cellular morphology. These derivatives were found to disrupt HCEC’s membrane integrity and promoted apoptosis but non-genotoxic on HCEC’s DNA.